“Moscovites” - “Non-Moscovites”: from the dichotomy of opposition to the search for identity - Yuriy M. Pochta (RUDN Journal of Political Science)
The article examines the role of Moscow as the capital of the Russian Federation, as a megalopolis in changing and supporting the value-civilizational specifics of Russian society, its influenceontheprocessofformationofthe Russiancivilizationalidentity, ensuringthefullsovereignty of the country. The methodology of the work includes civilizational analysis, concepts developed within the framework of identitarian research, recognition of the politicization of civilizational meanings, recognition of the civilizational meaning of identity as a key factor, recognition of the multiplicity of ways of political development as opposed to a linear normative model. The dynamic process of the formation of Russian identity is considered on the example of Moscow in sociocultural, economic, and political terms. The analysis of the results of student surveys in focus groups is given on who they can say “we” about, on the problem of resource allocation between Moscow and the regions, on obstacles to improving mutual understanding between Moscow and the regions, on what unites Moscovites and other Russians. It is shown that students give priority to the national civic identity and the value of the lifestyle associated with this identity. The problem of social justice in relations between Moscow and the regions attracts great attention of young people. The recommendation on the need for the practice of creating a single value field (institutional means, the role of religious organizations, the use of the discourse of an external threat) for a stable systemic connection between Moscow and the whole country in the context of identity politics is substantiated.